有情与无情 ：论《芈月传》中宣太后的两难抉择 = An entanglement of love and politics : the choice dilemma of Queen Dowager Xuan in the legend of Mi Yue - 刘凯丽 Lau, Kai Li (2017)
电视剧《芈月传》是以秦宣太后为原型的历史剧。芈月作为中国第一位垂帘听政的太后，执政时期长达四十一年之久。她的政治功业不比武后或慈禧太后逊色，却遭到历史埋没其光芒。本文梳理芈月在历史和文学作品中富有传奇色彩的人生，从中揭示其性格特点。身为一位政治人物，“无情”是围绕着芈月一生的关键词。然而，“有情”是电视剧为这位传奇人物注入的新血液。以郑晓龙执导的《芈月传》为依据，本文分析秦宣太后在剧中与三个男人的情感纠葛，并探讨她在政治与情爱两者之间所作的权衡。由于《芈月传》获得的评价褒贬不一，本文也探究该剧的超越性和局限性。The archetype of Mi Yue in historical serial drama The Legend of Mi Yue is the Queen Dowager Xuan of Qin. She was the first female figure who had attended to state affairs for 41 years in history. Even though her political leadership is comparable to Empress Wu and Empress Dowager Cixi, this fascinating figure remained long forgotten by the history. This thesis analyse the legendary life of Mi Yue from both aspects of history and literature works. As a political figure, power was a key factor in Queen Dowager Xuan’s life. However, the once merciless politician in history is represented with a more feminine side in literature works. With reference to The Legend of Mi Yue directed by Zheng Xiaolong, this thesis will discuss the relationship between Mi Yue and the three men in her life, and further examines her choice dilemma between the emotional entanglements and politics. There are mixed notices of The Legend of Mi Yue, hence this thesis will offer some insights of the development of such historical dramas in the future by looking into the breakthroughs and limitations of it.